High-level expression of thermostable cellulolytic enzymes in tobacco transplastomic plants and their use in hydrolysis of an industrially pretreated Arundo donax L. biomass. Issue 1 (December 2016) - Castiglia, Daniela; Sannino, Lorenza; Marcolongo, Loredana; Ionata, Elena; Tamburino, Rachele; Stradis, Angelo; Cobucci-Ponzano, Beatrice; Moracci, Marco; Cara, Francesco; Scotti, Nunzia
Abstract Background Biofuels production from plant biomasses is a complex multi-step process with important economic burdens. Several biotechnological approaches have been pursued to reduce biofuels production costs. The aim of the present study was to explore the production in tobacco plastome of three genes encoding (hemi)cellulolytic enzymes from thermophilic and hyperthermophilic bacterium andArchaea, respectively, and test their application in the bioconversion of an important industrially pretreated biomass feedstock (A. donax ) for production of second-generation biofuels. Results The selected enzymes, endoglucanase, endo-β-1, 4-xylanase and β-glucosidase, were expressed in tobacco plastome with a protein yield range from 2 % to more than 75 % of total soluble proteins (TSP). The accumulation of endoglucanase (up to 2 % TSP) gave altered plant phenotypes whose severity was directly linked to the enzyme yield. The most severe seedling-lethal phenotype was due to the impairment of plastid development associated to the binding of endoglucanase protein to thylakoids. Endo-β-1, 4-xylanase and β-glucosidase, produced at very high level without detrimental effects on plant development, were enriched (fourfold) by heat treatment (105.4 and 255.4 U/mg, respectively). Both plastid-derived biocatalysts retained the main features of the native or recombinantly expressed enzymes with interesting differences. Plastid-derived xylanase and β-glucosidase resulted more thermophilic than theE. coli recombinant and native counterpart, respectively. Bioconversion experiments, carried out at 50 and 60 °C, demonstrated that plastid-derived enzymes were able to hydrolyse an industrially pretreated giant reed biomass. In particular, the replacement of commercial enzyme with plastid-derived xylanase, at 60 °C, produced an increase of both xylose recovery and hydrolysis rate; whereas the replacement of both xylanase and β-glucosidase produced glucose levels similar to those observed with the commercial cocktails, and xylose yields always higher in the whole 24–72 h range. Conclusions The very high production level of thermophilic and hyperthermophilic enzymes, their stability and bioconversion efficiencies described in this study demonstrate that plastid transformation represents a real cost-effective production platform for cellulolytic enzymes.